BRICS Countries in Political Consciousness of Russian Citizens - S. Yu. Belokonev; T. V. Evgenieva; V. V. Titov; Z. R. Usmanova (Vestnik MGIMO-Universiteta)
The article analyzes the Russian citizens’ perceptions of BRICS countries. The authors focus on the cognitive, emotional, behavioral, and symbolic aspects characterizing BRICS countries in political consciousness of the Russians as well as common stereotypes, intentions, and associations. Since the Russian Federation has political and economic interests in cooperation with the BRICS countries, it is important to study representations of Brazil, India, China and South Africa in Russian consciousness and identify the possibilities of their transformation. Proceeding from the results of qualitative politico-sociological (a series of focused interviews) and politico-psychological (projective tests) studies held in 2016-2018 the authors conclude that the emotional component prevails in the structure of Russian citizens’ perception about of Brazil, India, China and South Africa. The image of China appears to be the most complicated and multidimensional, with the key elements being the “thousand-year history”, the “great culture” and the recognition of the geopolitical power of this state. The images of India and Brazil among the Russians have a significantly more amorphous character, but at the same time hold a moderately positive emotional connotation. The image of South Africa is the most fragmented, devoid of stable emotional valence and bright associations. It is remarkable that the perception of the BRICS countries by the majority of respondents is primarily influenced by implicit factors which manifest in appeal to stereotypes and associations (India – cinema, Brazil – football, etc.). Dynamic factors, determined by political agenda, play a minor role forming the images of the BRICS countries. A noticeable feature of their representation among the Russians is the blurring of the “image of due” and “image of the future”, as well as the minimal role of the political component (with exception of China). Therefore, it is necessary to change the information policy for the countries studied. In order to enhance the understanding of significance and relevance of cooperation with the BRICS states among the Russian citizens, it seems to be necessary 1) to build a positive image of political relations with them; 2) to cement an image of a “partner” and an “ally” in mass media, both on a rational and an unconscious level of political perception.